1998
DOI: 10.1002/(sici)1097-4547(19980215)51:4<423::aid-jnr2>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system endothelium in neuroinflammatory, neuroinfectious, and neurodegenerative disease

Abstract: Accumulating evidence points toward a significant role for the microvascular endothelium in the pathogenesis of several neurologic conditions. This review highlights those biochemical, anatomical, and physiological features of the endothelium thought to be dysfunctional in these disease states, and elaborates on novel treatment modalities that target the endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…Increasing evidence has demonstrated that pathological changes in the microvasculature play a role in neurodegenerative diseases and especially in AD (Andjelkovic and Pachter 1998). Elevated levels of pro-inflammatory cytokines, such as TNF-α and IL-1β, have been found to be released by microvessels in the AD brain as compared to microvessels from age-matched controls (Grammas and Ovase 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that pathological changes in the microvasculature play a role in neurodegenerative diseases and especially in AD (Andjelkovic and Pachter 1998). Elevated levels of pro-inflammatory cytokines, such as TNF-α and IL-1β, have been found to be released by microvessels in the AD brain as compared to microvessels from age-matched controls (Grammas and Ovase 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their critical role as regulators of cerebral homeostasis, perturbations of the microvascular endothelium are closely linked to the pathophysiology of neuroinflammatory and neurodegenerative disease states, including AD [178][179][180].…”
Section: Microvascular Endothelium As Mediator Of Inflammatory Processesmentioning
confidence: 99%
“…Similar events occur in psoriatic skin, where ECs actively display adhesion molecule for leukocyte recruitment, form new vessels, and mediate inflammation (94). In multiple sclerosis, transendothelial migration of activated leukocytes is one of the earliest abnormalities, and exposure of the endothelium to immune cell-derived IFN-␥, TNF-␣, and IL-1␤ disrupts the blood-brain barrier by disorganizing cell-cell junctions, enhancing leukocyte endothelial adhesion and migration, and increasing expression of MHC class II Ags (95). The endothelium promotes gut inflammation through comparable mechanisms.…”
Section: Ec-mediated Immune Dysfunction and Diseasementioning
confidence: 99%